Divided Loyalties Displacement, belonging and citizenship among East Timorese in West Timor - Damaledo, Andrey (ANU Press, 2018)
Drawing on extensive ethnographic fieldwork, this study explores the ideas of belonging and citizenship among former pro-autonomy East Timorese who have elected to settle indefinitely in West Timor. The study follows different East Timorese groups and examines various ways they construct and negotiate their socio-political identities following the violent and destructive separation from their homeland. The East Timorese might have had Indonesia as their destination when they left the eastern half of the island in the aftermath of the referendum, but they have not relinquished their cultural identities as East Timorese. The study highlights the significance of the notions of origin, ancestry and alliance in our understanding of East Timorese place-making and belonging to a particular locality. Another feature of belonging that informs East Timorese identity is their narrative of sacrifice to maintain connections with their homeland and move on with their lives in Indonesia. These sacrificial narratives elaborate an East Timorese spirit of struggle and resilience, a feature further exemplified in the transformation of their political activities within the Indonesian political system.